1996
DOI: 10.1901/jaba.1996.29-321
|View full text |Cite
|
Sign up to set email alerts
|

An Alternating Treatments Comparison of Two Intensive Interventions for Food Refusal

Abstract: We compared two treatment packages involving negative reinforcement contingencies for 3 children with chronic food refusal. One involved physically guiding the child to accept food contingent on noncompliance, whereas the other involved nonremoval of the spoon until the child accepted the presented food. Subsequent to baseline, an alternating treatments comparison was implemented in a multiple baseline design across subjects. After each child had been exposed to at least nine sessions of each treatment conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
178
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(194 citation statements)
references
References 17 publications
15
178
0
1
Order By: Relevance
“…Specialized techniques proven to be effective by behavioral therapists include distraction to avoid gagging, 49 use of a chaser to overcome "pocketing" (food retained in the cheeks), 72 following the mouth of the child with the spoon, or guiding the child physically to accept food. 73 Recently, medications to suppress visceral hyperalgesia have helped establish normal feeding in tube-fed children. 74 …”
Section: Management Of Fear Of Feedingmentioning
confidence: 99%
“…Specialized techniques proven to be effective by behavioral therapists include distraction to avoid gagging, 49 use of a chaser to overcome "pocketing" (food retained in the cheeks), 72 following the mouth of the child with the spoon, or guiding the child physically to accept food. 73 Recently, medications to suppress visceral hyperalgesia have helped establish normal feeding in tube-fed children. 74 …”
Section: Management Of Fear Of Feedingmentioning
confidence: 99%
“…One intervention reported to be effective in such settings is escape extinction (i.e., nonremoval of the spoon) combined with differential reinforcement of acceptance (DRA; e.g., Ahearn, Kerwin, Eicher, Shantz, & Swearingin, 1996). Although previous studies have shown that parents can be trained to implement escape extinction after intervention gains are obtained by trained therapists (e.g., Ahearn et al), little research has systematically evaluated parents' ability to serve as initial change agents.…”
Section: Journal Of Applied Behavior Analysismentioning
confidence: 99%
“…A multi-component treatment package consisting of positive reinforcement and escape extinction is the most commonly used intervention for this problem (e.g., Ahearn, Kerwin, Eicher, Shantz, & Swearingin, 1996;Babbitt et al, 1994;Cooper et al, 1995;Kerwin, Ahearn, Eicher, & Burd, 1995;Piazza, Patel, Gulotta, Sevin, & Layer, 2003). The positive reinforcement component typically involves providing the child with access to preferred stimuli (e.g., food, toys, praise, tokens) for desired eating behavior (i.e., accepting or swallowing bites).…”
mentioning
confidence: 99%